Open and closed penalty kick strategies in intermediate soccer player - J. M. Castillo; A. Oña; A. Raya; A. Bilbao; E. Serra (Asociación Española de Ciencias del Deporte, 2010)
This study investigates the efficacy of intermediate penalty kickers by comparing the effect of applying an automated WiFi (Wireless Fidelity)  system on the field of play to simulate a strategy that takes account of goalkeeper action (open) with another for which goalkeeper strategy is irrelevant (closed). Intermediate penalty kickers (n=12) took a pretreatment test of 32 kicks in a "real-play" situation with intermediate goalkeepers (n=3). We established two groups of kickers who underwent 11 treatment sessions using different strategies and then conducted a posttreatment test. The variables we measured were the number of goals scored, whether the direction of the shot was the same or different from the direction of the goalkeeper's move (DDG), ball speed and the duration of the kicking movement. The results suggest the goalkeepers demonstrated a greater capacity to identify advance cues when faced with CG (closed strategy group) kickers and that OG (open strategy group) kickers achieved lower ball speeds when modifying the contact surface of the kick. Key Words:  penalty kick, anticipation, decision-making, field, training.